2016
DOI: 10.2147/tcrm.s110363
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological, and radiological characteristics of solitary ground-glass opacity lung nodules on high-resolution computed tomography

Abstract: BackgroundLung nodules are being detected at an increasing rate year by year with high-resolution computed tomography (HRCT) being widely used. Ground-glass opacity nodule is one of the special types of pulmonary nodules that is confirmed to be closely associated with early stage of lung cancer. Very little is known about solitary ground-glass opacity nodules (SGGNs). In this study, we analyzed the clinical, pathological, and radiological characteristics of SGGNs on HRCT.MethodsA total of 95 resected SGGNs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
4
21
1
Order By: Relevance
“…Numerous studies proved that the CT findings were useful for evaluating the histological nature of the tumors and correlated with the IASLC/ATS/ERS classification [ 8 10 ]. Our results showed that benign lesions only accounted for 7.1%, the reason may be the selection of candidate patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies proved that the CT findings were useful for evaluating the histological nature of the tumors and correlated with the IASLC/ATS/ERS classification [ 8 10 ]. Our results showed that benign lesions only accounted for 7.1%, the reason may be the selection of candidate patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…mGGNs are more frequently pathologically diagnosed as invasive adenocarcinoma; however, AIS and MIA more often present as pGGNs on the contrary. 8 In malignant part-solid GGNs, the solid part histologically represents invasion, whereas the pure GGO areas are considered as lepidic components of adenocarcinoma. Solid transformation of GGNs is thus considered a strong indicator of malignancy.…”
Section: Categories Of Ggnsmentioning
confidence: 99%
“…Based on their density features on computed tomography (CT) images, cancerous nodules can be generally divided into solid and subsolid nodules, each with significantly different morphological and pathological features [3]. Several studies have been conducted on the differential diagnosis of benign and malignant subsolid nodules [4][5][6][7][8] and the solid ones [9][10][11][12][13]. Compared with subsolid lung cancerous nodules, the solid ones have a worse prognosis because of their rapid growth [14][15][16] and earlier metastases [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%